Comparative Analysis of Binary Option Law in Indonesia and United States of America - Tiara Nurfathia; Patricia Rinwigati (Unnes Law Journal, 2024)
Binary option, which was originally applied from the United States (US), has become a public discussion in Indonesia due to various cases. This happened due to there was an Indonesian YouTuber who introduced Binary Option investment, and many people joined the trade. However Binary Option trading is illegal in Indonesia. In order to respond to these cases, it is crucial to understand a comprehensive picture particularly on legality, case and regulatory framework. It is necessary to obtain a clear description of the country of origin of Binary Options, namely the United States. This research is descriptive in nature with the type of normative juridical research through a comparative legal approach with qualitative analysis methods. The result of this research shows that a comparison of Binary Option law in Indonesia and the US can be identified from the differences in terms of legality, the supervising institution, the regulations, and the criminal acts that occurred along with the sanctions. Unlike the US, which legalizes Binary Option trading, in Indonesia Binary Option is not a part of legal investments, instead it is classified as gambling. US have an anti-fraud regulations about Binary Option trading, while Indonesia does not have one, but explicitly can use another laws.